Resistance training-induced gains in rate of force development are maintained during training cessation: a meta-analysis - Grgic, J.; Grgic, I. (Strength and Conditioning Journal, 2023)
The present meta-analysis examined the effects of resistance training on increasing the rate of force development (RFD), followed by exploring the changes in RFD occurring during training cessation. Five databases were searched to find eligible studies. Their methodological quality was evaluated using the Downs and Black checklist. The data were pooled in a random-effects meta-analysis. Seven studies with 11 training groups were included in the meta-analysis. All studies were classified as being of good or moderate quality. Resistance training increased RFD (d: 0.24; 95% confidence interval [CI]: 0.09-0.38). There was no significant difference in RFD between the postintervention and postdetraining periods (d: -0.02; 95% CI: -0.10-0.06). In subgroup meta-analyses, there was no significant difference (all p > 0.05) between the postintervention and postdetraining RFD when categorized according to detraining duration (up to 4 weeks versus 7-16 weeks) or participants' training status (untrained versus trained). This meta-analysis demonstrated that resistance training effectively increases RFD. More importantly, the results also indicated that gains in RFD are maintained after detraining. Thus, unlike a few other resistance training-induced adaptations (e.g., increases in muscular strength and muscular endurance), it seems that gains in RFD are preserved during a detraining phase.